Open J Environ Biol 2017
DOI: 10.17352/ojeb.000005
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Pollution Measured with an online Monitoring System using Daphnia

Abstract: Arsenic is a common pollutant in many water reservoirs around the world and is the cause of human mortality in many countries. The microcrustacean Daphnia can be cultured easily and is sensitive to many toxic substances including As. This bioindicator is the basis of the Daphniatox instrument which uses computerized image analysis of swimming organisms in real time. Fourteen endpoints are evaluated including motility, swimming velocity, orientation with respect to light or gravity as well as several cell size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…There are currently no studies that explain why there may be an increase in responses of the selective behavioral parameters induced by dietary-As exposure in a media/environment with limited P condition. However, in the study by Häder and Erzinger, they observed differential effects (decrease or no effect) on the 14 swimming behavioral end points of D. magna exposed to media As.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…There are currently no studies that explain why there may be an increase in responses of the selective behavioral parameters induced by dietary-As exposure in a media/environment with limited P condition. However, in the study by Häder and Erzinger, they observed differential effects (decrease or no effect) on the 14 swimming behavioral end points of D. magna exposed to media As.…”
Section: Resultsmentioning
confidence: 90%
“…magna exposed to media As. Häder and Erzinger attributed the reduction in swimming behavior to oxidative stress and partly to feeding since the organisms were not fed during the experimental period. The responses in selective behavioral parameters of D.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation